1974
DOI: 10.1002/pol.1974.180120211
|View full text |Cite
|
Sign up to set email alerts
|

Atomic mechanism of fracture of solid polymers

Abstract: Macromolecular chain scission under mechanical stress has been studied by infrared spectroscopy. The dependence of accumulation of chemical bond scissions on temperature T and uniaxial tensile stress σ has been investigated. The rate constant K for bond dissociation under mechanical stress has been found to obey the modified Arrhenius equation: K = K0 exp{ − (EA − ασ)/RA}. The quantitative connection between the rate constant for bond dissociation and mechanical lifetime τ has been established. Analysis of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
124
0
3

Year Published

1981
1981
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 221 publications
(136 citation statements)
references
References 13 publications
9
124
0
3
Order By: Relevance
“…To expose the deteriorated region near the tip electrode so that spectroscopic 14 study could be made, it was necessary to cut the sample into 1 00-micron thick slices. This introduces physical damage and may have influenced the results, especially as it is known that mechanical working of polymers can generate free radicals [Zhurkov et al (1974)]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To expose the deteriorated region near the tip electrode so that spectroscopic 14 study could be made, it was necessary to cut the sample into 1 00-micron thick slices. This introduces physical damage and may have influenced the results, especially as it is known that mechanical working of polymers can generate free radicals [Zhurkov et al (1974)]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition it has also been shovvn that ruptured bonds can localise into micro regions forming sub-microvoids Mich have been found to lead to the physical breakdown of the polymer. [Zhurkov et al (1974)] Crystallinity There has been a significant amount of published work carried out with…”
Section: -46mentioning
confidence: 99%
“…For polymers it was not clear whether covalent bonds within molecules were being broken or van der Waal bonds between polymer molecules, allowing the latter to slip past one another. However, in 1974 Zhurkov and Kursukov used infrared spectroscopy to monitor the breaking of covalent polymer bonds and showed that this process was paramount in determining the dependence of fracture on stress [25]. They also showed that the values of U o calculated from the dependence of fracture time on temperature in Eq.…”
Section: If Dry Chloride Of Silver In Powder Be Triturated In a Mortamentioning
confidence: 99%
“…[24,25]. From the above it can be seen that, by the end of the 1950s, the stress-augmented thermal activation approach pioneered by Prandtl and Eyring had been successfully used in models of plastic deformation, liquid viscosity, kinetic friction, and chemical bond dissociation.…”
Section: Early Historymentioning
confidence: 99%
See 1 more Smart Citation